Changes in the assembly and functional adaptation of endophytic microbial communities in Amorphophallus species with different levels of resistance to necrotrophic bacterial pathogen stress - Min Yang; Ying Qi; Penghua Gao; Lifang Li; Jianwei Guo; Yongteng Zhao; Jiani Liu; Zebin Chen; Lei Yu (Communications Biology)
Abstract Pcc is one of the key pathogenic factors responsible for destructive soft rot in konjac. To date, the assembly and functional adaptation of the plant endophytic microbiome under Pcc stress remain poorly understood. Here, we found that Pcc stress leads to rapid reorganization of the endogenous microbiome in multiple organs of both susceptible and resistant konjac plants. Under Pcc stress, the negative interactions within the bacterial-fungal interdomain network intensified, suggesting an increase in ecological competition between bacterial and fungal taxa. We further discovered that the relative abundance dynamics of the classes Dothideomycetes and Sordariomycetes, as core fungal taxa, changed in response to Pcc stress. By isolating culturable microorganisms, we demonstrated that 46 fungal strains strongly inhibited the growth of Pcc. This implies that endophytic fungal taxa in konjac may protect the host plant through ecological competition or by inhibiting the growth of pathogenic bacteria. Metagenomic analysis demonstrated that microbial communities associated with resistant Amorphophallus muelleri exhibited unique advantages over susceptible Amorphophallus konjac in enhancing environmental adaptability, regulating plant immune signaling, strengthening cell walls, and inducing defense responses. Our work provides important evidence that endophytic fungal taxa play a key role in the host plant’s defense against necrotizing bacterial pathogens.